Exposing a nation-centric view on the German internet : a change in perspective on AS-level - Matthias Wählisch and Thomas C. Schmidt and Markus de Brün and Thomas Häberlen (Lecture notes in computer science, 2012)
The Internet has matured to a critical infrastructure in many countries. The national importance of routing motivates us to study the AS-level subgraph that is relevant for a country. In this paper, we report on a methodology and tool chain for identifying and classifying a 'national Internet', and evaluate detailed results for the example of Germany. Our contribution (a) identifies the ASes that are important for the country, (b) classifies these ASes into functional sectors, (c) constructs the AS routing graph of a country as well as subgraphs of specific sectors, and (d) analyzes structural dependencies between key players. Our methods indicate the importance of examining individual IP-blocks held by individual organizations, as this reveals 25% more stakeholders compared to only looking at prefixes. We quantify the centrality of ASes with respect to specific sectors and the robustness of communication communities. Our results show that members of sectoral groups tend to avoid direct peering, but inter-connect via a small set of common ISPs. Even though applied for Germany here, all methods are designed general enough to work for most countries, as well.
Keywords: Autonomous System; Critical Infrastructure; Tool Chain; Sectoral Group; Relative Betweenness